Preface to the book This is life: the journey of uniportal VATS - D’Amico, Thomas A. (Video-Assisted Thoracic Surgery; Vol 1 (September 2016): Video-Assisted Thoracic Surgery, 2016)
Thoracoscopic lobectomy was introduced without the support of prospective randomized trials; however, the advantages of thoracoscopic lobectomy were demonstrated through multi-institutional and propensity-matched studies, proving the quality of life advantages, safety advantages, and cost advantages, compared to thoracotomy. Prospective randomized trials would now be difficult to complete to due lack of equipoise. Thoracoscopic lobectomy has emerged as the standard of care for early stage lung cancer and is utilized extensively for locally advanced lung cancer in centers of excellence. Throughout the investigation of the potential for thoracoscopic lobectomy to improve outcomes, the focus on technical aspects centered on limiting the size of the access incision, but more importantly, avoiding rib spreading with a retractor. Surgeons may have used 4 ports, or 3 ports or 2 ports, and robotic procedures may have employed with up to 5 ports, but the difference in the number of ports was never considered in assessing outcomes.